AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL 70% DAUN ASHITABA (Angelica keiskei) SECARA IN VIVO DENGAN PENGINDUKSI KARAGENAN - Haka As'ada; Yardi Saibi; Hendri Aldrat (JFL : Jurnal Farmasi Lampung, 2018)
Ashitaba leaves (Angelica keiskei) or also known as tommorow's leaf is plant that known to have various health benefit, one of them is as an anti-inflammatory activity. The anti-inflammatory activity of ashitaba leaves has been known through in vitro assays. This study aims to determine the anti-inflammatory activity of 70% ethanol extract of ashitaba leaves through in vivo assay. Anti-inflammatory activity was performed on white male rat of Sprague dawley strain with induction method of edema on rat's foot using 1% carrageenan 0.2 ml. Rats were divided into 5 groups. The negative control group was given a 0.5% Na-CMC suspension, a positive control group was given sodium diclofenac suspension of 5.14 mg / kgBW, and the test group was given 70% ethanol extract of ashitaba leaves at a dose of 1000; 2000; and 4000 mg / kgBW suspended in 0.5% Na-CMC. The results showed that in that dose range the 70% ethanol extract of ashitaba leaves had anti-inflammatory activity that did not depend on the dose. Percentage of edema of 70% ethanol extract of ashitaba leaves dose 1000; 2000; 4000 mg / kgBB was significantly different with negative control (p ≤ 0,05) and had percentage of edema inhibition respectively 83,95%, 79,01%, and 80,25%. The results of this study showed that 70% ethanol extract of ashitaba leaves have anti-inflammatory activity. Keywords: Ashitaba, Angelica keiskei, tommorow's leaf, anti-inflammatory, carrageenan.